A highly sensitive fluorescence biosensor for detection of Staphylococcus aureus based on HCR-mediated three-way DNA junction nicking enzyme assisted signal amplification. Issue 21 (27th September 2021) - Zhang, Chuyan; Luo, Zewei; Wu, Mengfan; Ning, Wei; Tian, Ziyi; Duan, Yixiang; Li, Yongxin
Abstract : A novel biosensor for highly sensitive detection of Staphylococcus aureus ( S. aureus ) was constructed based on the synergistic amplification of hybridization chain reaction (HCR) and nicking enzyme. Abstract : Sensitive and efficient monitoring of food-borne bacteria is of great importance for food safety control. Herein, a novel biosensor for highly sensitive detection of Staphylococcus aureus ( S. aureus ) was constructed by combining hybridization chain reaction (HCR) and nicking enzyme. Different from the upstream-downstream based circuit, the proposed biosensor integrated HCR circuit and three-way DNA junction nicking enzyme assisted signal amplification (3WJ-NEASA) into a virtuous circle of promotion. In the HCR-mediated 3WJ-NEASA sensing strategy, target DNA of S. aureus initiated the self-assembly between HCR hairpins (H1 and H2), which exposed the gap to capture molecular beacon (MB) and construct the 3WJ structure. Meanwhile, MB increased the stability of HCR nanowires and enhanced the efficiency of the HCR circuit, and thus more 3WJ-NEASA circuits were generated in HCR nanowires. Benefiting from the synergistic amplification coupling HCR and 3WJ-NEASA, this isothermal biosensor can detect as low as 6.7 pM of target DNA in one step within only 30 min. Furthermore, the HCR-mediated 3WJ-NEASA assay has been applied in the detection of S. aureus with a limit of detection (LOD) as low as 1.2 × 10 1 cfu mL −1, and has exhibited reliable practicability in spiked milk. It is the first time that a DNA biosensor combining HCR and 3WJ-NEASA for dual signal amplification was developed and has been adopted to the sensitive analysis of food-borne bacteria. Additionally, this strategy can serve as a universal platform for monitoring other analytes, and therefore possesses broad application prospects in food safety and environmental monitoring.